PANORAMA HISTORY OF SOCIAL EXCHANGE THEORY: SEJARAH PANORAMA TEORI PERTUKARAN SOSIAL - Sufyanto, Sufyanto (Universitas Muhammadiyah Sidoarjo, 2024)
This study discusses the history and development of social exchange theory, focusing on basic concepts such as giving, receiving, and returning. This theory is influenced by various figures, including Marcel Mauss, George Homans, and Peter Blau. Mauss in